The Influence of Brand Image and Green Marketing on Purchasing Decisions Which are Mediated by Customer Satisfaction in the Coffee Shop Industry in Denpasar - ERAWAN, Putu Yuke Prabandari; WAHYUNI, Ni Made; INDIANI, Ni Luh Putu (International Journal of Environmental, Sustainability, and Social Science, 2024)
The problem of purchasing decisions occurs in several coffee shops in Denpasar City. The thing that encourages consumers to keep coming to one coffee shop is because the company creates a brand image of its environmentally friendly products which has an impact on consumer purchasing decisions for these coffee products. This study aims to analyze the effect of brand image and customer satisfaction on purchasing decisions with customer satisfaction as a mediating variable in the coffee shop industry in Denpasar City. The population in this study were all consumers who had visited one of the coffee shops in Denpasar City. The sample used was 80 respondents who had visited one of the coffee shops in Denpasar City. The data analysis method used used descriptive statistics and inferential statistics using Partial Least Square (PLS). The results of this study found that brand image has a negative and insignificant effect on purchasing decisions. Brand image has a negative and insignificant effect on customer satisfaction. Green marketing has a positive and significant effect on purchasing decisions. Green marketing has a positive and significant effect on customer satisfaction. Customer satisfaction has a significant positive effect on purchasing decisions. Customer Satisfaction perfectly mediates the effect of brand image on purchasing decisions. Customer Satisfaction perfectly mediates the effect of green marketing on purchasing decisions.